A Comparative Assessment of Life-Cycle Greenhouse Gas Emissions from Hypothetical Electric Airport Transportation Services in Thailand - J Koiwanit (My University, 2018)
Global warming is an increase of average temperature in the atmosphere, which causes adverse effects on the environment. Carbon dioxide (CO2) from transportation sector is one of the main contributors of the overall greenhouse gases (GHG). To cope with this issue, electric car services are increasingly seen as popular alternative modes of green transportation especially for urban cities as it is more flexible, more environmentally-friendly, and less expensive than the use of conventional vehicles. The study analyses and compare the hypothetical electric car systems from airport transportation services. Center of Environmental Science of Leiden University (CML) 2001, the Life Cycle Impact Assessment (LCIA) method, is applied to convert life cycle inventory data into environmental impacts. The observed results showed that the electric shuttle bus had the highest impact in global warming potential (GWP) compared to other transportation types. Alternatively, this Life Cycle Assessment (LCA) study that evaluated different transportations provided important information for decision makers on quantifying the differences between each scenario.
Keywords: Carbon dioxide equivalent; Global-warming potential; Cycling; Greenhouse effect; Electric Vehicles and Infrastructure